2013
DOI: 10.15596/arms.2013.22.2.43
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lumbar Artery Perforator Flap for Reconstruction of Back Ulcer: Clinical Study with Computed Tomographic Angiography

Abstract: Un-healing and centrally located defect on back area, it is sometimes a challenge for the reconstructive surgeon. Although skin grafts are considered as the first choice for reconstruction of large skin defect on the back region, it is not always helpful but vascularized flaps provide a superior functional and aesthetic outcome. The present study was designed to investigate the clinical anatomy of the lumbar artery perforator flap to reconstruct back ulcer. Materials and Methods: Clinical anatomy study was und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…4,[7][8][9][10][11][12]15 The observed variation in previously published work is likely due to the various methods used to collect data including cadaveric dissection techniques, 2D angiography, 3D angiography, and preoperative is is the first study of its kind to use 3D angiography and MIMICS software to characterize the LAs though the creation of 3D models of the microvasculature and to combine results from multiple cadavers. Using this technique, we have determined that perforators arising from the LAs pierce the thoracodorsal fascia in a predictable fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[7][8][9][10][11][12]15 The observed variation in previously published work is likely due to the various methods used to collect data including cadaveric dissection techniques, 2D angiography, 3D angiography, and preoperative is is the first study of its kind to use 3D angiography and MIMICS software to characterize the LAs though the creation of 3D models of the microvasculature and to combine results from multiple cadavers. Using this technique, we have determined that perforators arising from the LAs pierce the thoracodorsal fascia in a predictable fashion.…”
Section: Discussionmentioning
confidence: 99%
“…This flap can be used as a pedicled flap to reconstruct soft tissue defects in the lumbosacral region [2][3][4][5] including closure of myelomeningocele, a complex congenital malformations of the central nervous system, exposed spine, and other soft tissue defects in the back. 6,7 As a free flap, the LA perforator flap is a possible option for use in autologous breast reconstruction. 8 Although there have been a number of reports on the use of the LA perforator (LAP) flap for closure of lumbosacral defects and breast reconstruction, 8 there have been few anatomical studies to document the anatomy of the LA perforators.…”
mentioning
confidence: 99%
“…The lumbar artery perforator (LAP) flap was first described in the literature by Kroll and Rosenfeld in 1988 as a new type of flap based on unnamed perforators arising near the midline of the lower back region. Since that time, additional studies have demonstrated the presence of perforators arising from four‐paired lumbar arteries, around which pedicled or free fasciocutaneous flaps can be designed . The first report of using the LAP flap in autologous breast reconstruction was described in 2003 by de Weerd, et al Since that time, Peters et al, and Seth and Greenspun have both reported on their early experience with the LAP flap for autologous breast reconstruction, outlining their technique and overall outcomes.…”
Section: Alternative Flaps For Microsurgical Breast Reconstructionmentioning
confidence: 99%